Cold chain analysis of the fish auction place process in maintaining the quality of fish products in Kali Baru - Purwoko, Harry; Baskoro, Dian Anom; Purba, Okin Ringan; Saputra, Rangga Juliardy; Rahmawati, Dina (ARKA INSTITUTE, 2025)
Fishery commodities are one of the commodities that have not been widely studied in terms of their distribution system. The cold chain system is important in the distribution system for fish products. The purpose of this study was to evaluate the effectiveness of the cold chain system at the trader level at the Kalibaru Barat Fish Landing Place (TPI). Qualitative methods were used in this study, and qualitative data were collected through observation and interviews with fish traders and consumers in traditional markets. The results showed that the West Kalibaru Fish Auction Center is the largest source of fish feed in the Cilincing area. The distribution chain shows that the West Kalibaru Fish Auction Center plays an important role in distributing fish products directly to consumers and fish restaurants. Consumers are highly dependent on Kalibaru Barat Fish Auction Market for their daily food supply. At Kalibaru Barat Fish Auction Market, the cold chain system has not been properly implemented, and the traders at Kalibaru Barat Fish Auction Market have a damaged cold chain system. The importance of fish traders' knowledge and motivation regarding the use of ice to maintain fish quality and freshness, as well as the need to improve the quality of facilities and infrastructure at the fish auction site to increase productivity at the Kalibaru Market, is still very much needed so that traders do not sell on the side of the market or on the sidewalk using tarpaulin roofs.